Accuracy of emergency medical dispatchers' subjective ability to identify when higher dispatch levels are warranted over a Medical Priority Dispatch System automated protocol's recommended coding based on paramedic outcome data. Issue 8 (25th July 2007) - Clawson, Jeff; Olola, Christopher H O; Heward, Andy; Scott, Greg; Patterson, Brett
Abstract : Objectives: To establish the accuracy of the emergency medical dispatcher's (EMD's) decisions to override the automated Medical Priority Dispatch System (MPDS) logic-based response code recommendations based on at-scene paramedic-applied transport acuity determinations (blue-in) and cardiac arrest (CA) findings. Methods: A retrospective study of a 1 year dataset from the London Ambulance Service (LAS) National Health Service (NHS) Trust was undertaken. We compared all LAS "bluing in" frequency (BIQ) and cardiac arrest quotient (CAQ) outcomes of the incidents automatically recommended and accepted as CHARLIE-level codes, to those receiving EMD DELTA-overrides from the auto-recommended CHARLIE-level. We also compared the recommended DELTA-level outcomes to those in the higher ECHO-override cases. Results: There was no significant association between outcome (CA/Blue-in) and the determinant codes (DELTA-override and CHARLIE-level) for both CA (odds ratio (OR) 0, 95% confidence interval (CI) 0 to 41.14; p = 1.000) and Blue-in categories (OR 0.89, 95% CI 0.34 to 2.33; p = 1.000). Similar patterns were observed between outcome and all DELTA-level and ECHO-override codes for both CA (OR 0, 95% CI 0 to 70.05; p = 1.000) and Blue-in categories (OR 1.17, 95% CI 0 to 7.12; p = 0.597). Conclusion: This study contradicts the belief that EMDs can accurately perceive when a patient or situation requires more resources than the MPDS's structured interrogation process logically indicates. This further strengthens the concept that automated, protocol-based call taking is more accurate and consistent than the subjective, anecdotal or experience-based determinations made by individual EMDs.